2013
DOI: 10.1242/jcs.126003
|View full text |Cite
|
Sign up to set email alerts
|

The tudor protein survival motor neuron (SMN) is a chromatin-binding protein that interacts with methylated histone H3 lysine 79

Abstract: SummarySpinal muscular atrophy (SMA) is a muscular disease characterized by the death of motoneurons, and is a major genetic cause of infant mortality. Mutations in the SMN1 gene, which encodes the protein survival motor neuron (SMN), are responsible for the disease. SMN belongs to the Tudor domain protein family, whose members are known to interact with methylated arginine (R) or lysine (K) residues. SMN has well-defined roles in the metabolism of small non-coding ribonucleoproteins (snRNPs) and spliceosome a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 123 publications
(174 reference statements)
3
45
0
Order By: Relevance
“…SMN itself is recruited, through its N-terminal Tudor domain, to dimethylated histone H3K79 in the setting of the interphase centromere damage response [28]. Whether SMN is involved in executing this response or other forms of DNA repair, such as double-strand break repair, known to be mediated by another Tudor-domain protein, 53BP1, in an H3K79me-dependent manner [29], is a question that warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…SMN itself is recruited, through its N-terminal Tudor domain, to dimethylated histone H3K79 in the setting of the interphase centromere damage response [28]. Whether SMN is involved in executing this response or other forms of DNA repair, such as double-strand break repair, known to be mediated by another Tudor-domain protein, 53BP1, in an H3K79me-dependent manner [29], is a question that warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…58 The finding that the SMN protein recognizes methylated H3K79 indicates that there may be an epigenetic dimension to spinal muscular atrophy and that DOT1L may be important for motor neuron function. 57 Future research should determine the specific interplay and whether this function of DOT1L is confirmed in vivo. Several other key questions need further attention.…”
Section: Dot1l-h3k79 Methylation: Mechanisms Of Actionmentioning
confidence: 99%
“…SMN recognizes and interacts with methylated H3K79 in HeLa cells. 57 SMN is needed for the health and survival of motor neurons, and deficient SMN protein levels leads to spinal muscular atrophy. 58 The finding that the SMN protein recognizes methylated H3K79 indicates that there may be an epigenetic dimension to spinal muscular atrophy and that DOT1L may be important for motor neuron function.…”
Section: Dot1l-h3k79 Methylation: Mechanisms Of Actionmentioning
confidence: 99%
“…The SMN protein contains several functional domains including Gemin2-binding, nucleic acid binding, Tudor, self-association and cal-pain cleavage (Figure 1A) [8,9]. The interaction of SMN with Gemin2 has been suggested to be important for several SMN functions including small nuclear ribonucleoprotein (snRNP) biogenesis [19], signal recognition particle biogenesis [20], DNA recombination [21], motor neuron trafficking of mRNAs [22] and translation regulation [23].…”
Section: Structure–function Relationship In Smnmentioning
confidence: 99%
“…It remains to be seen if gems have specific functions or whether they are the signatures of an ordered nuclear organization forced by the spatial and temporal arrangement of other macromolecules. Other less studied SMN functions include detection of specific chromatin modifications [9], transcription [65,66], translation [23], signal transduction [67], stress granule formation [68] and macromolecular trafficking [69,70]. Motor neurons are particularly susceptible to the loss of SMN protein, although the reasons underlying this susceptibility are not well understood.…”
Section: Structure–function Relationship In Smnmentioning
confidence: 99%